2001
DOI: 10.1381/09608920160556698
|View full text |Cite
|
Sign up to set email alerts
|

Impartial Long-Term Review of Vertical Banded Gastroplasty in a Low Volume Community Hospital Practice

Abstract: Results from a low-volume community hospital general surgical practice are similar to those from specialized series. Obesity is so common, its non-surgical treatment so ineffective and the VBG so well established, that excluding this intervention from community hospitals is untenable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…There were no significant differences reported between BSCOE and non-BSCOE hospitals for patient mortality (0.17% vs 0.09%; P = 0.13), morbidity (6.3% vs 6.4%; P = 0.93), and duration of hospital stay (2.6 days vs 2.6 days; P = 0.83). Other studies of BSCOE hospital outcomes reported mor- 37 Fair + Nguyen et al 38 Fair + Murr et al 26 Fair + + Hollenbeak et al 25 Fair + + Encinosa et al 36 Good + Carbonell et al 35 Fair − Dimick et al 48 Fair + Weller et al 23 Good + + Kohn et al 39 Poor + Birkmeyer et al 24 Fair + + Livingston et al 46 Fair + Morino et al 56 Fair + O'Rourke et al 28 Fair − Parker et al 57 Fair + Voitk et al 29 Poor − Weller and Hannan 27 Fair + + * Quality: Good, Fair, or Poor. †(+) Presence or (−) absence of association.…”
Section: Hospital Volumes and Patient Outcomesmentioning
confidence: 99%
“…There were no significant differences reported between BSCOE and non-BSCOE hospitals for patient mortality (0.17% vs 0.09%; P = 0.13), morbidity (6.3% vs 6.4%; P = 0.93), and duration of hospital stay (2.6 days vs 2.6 days; P = 0.83). Other studies of BSCOE hospital outcomes reported mor- 37 Fair + Nguyen et al 38 Fair + Murr et al 26 Fair + + Hollenbeak et al 25 Fair + + Encinosa et al 36 Good + Carbonell et al 35 Fair − Dimick et al 48 Fair + Weller et al 23 Good + + Kohn et al 39 Poor + Birkmeyer et al 24 Fair + + Livingston et al 46 Fair + Morino et al 56 Fair + O'Rourke et al 28 Fair − Parker et al 57 Fair + Voitk et al 29 Poor − Weller and Hannan 27 Fair + + * Quality: Good, Fair, or Poor. †(+) Presence or (−) absence of association.…”
Section: Hospital Volumes and Patient Outcomesmentioning
confidence: 99%